A Randomized Control Study on Psycho-Education Group on Improving Health-Related Quality of Life of Chinese Persons with Major Neurocognitive Disorder. Issue 5 (19th October 2016) - Young, Kim-Wan
ABSTRACT: Objectives : People with a major neurocognitive disorder (PwND) are found to have a lower health related quality of life (HRQoL) than those without neurocognitive disorder. This research study aims to evaluate the effectiveness of a psycho-education group in improving the HRQoL of Chinese PwND. Methods : By adopting randomized control trial (RCT), Chinese PwND were randomly assigned to either a 10-session psycho-education group or the control group. Family caregivers of treatment group were encouraged to take part in two sessions focusing on the caring and communication skills. Control group and their family caregivers received standardized educational materials on basic information on neurocognitive disorder for them to read at home. Standardized assessment was conducted both with PwND and their caregivers independently to give the self-rated and caregiver-rated HRQoL of PwND in the pre- and post- treatment periods by a research assistant who was blind to the group assignment of the participants. Moreover, qualitative interviews were also conducted for ten participants and five family caregivers of the treatment group to identify those group elements relating to its effectiveness. Results : 2 × 2 repeated measures ANCOVA demonstrated that the treatment group (n = 32) was significantly more effective than the control group (n = 32) in improving the caregiver-rated HRQoL (F[1, 61] = 4.35, p = .04 < .05) with a moderate effect size, but not self-rated HRQoL, Qualitative analysis suggested several group elements relating to its effectiveness. Conclusions : This present RCT shows that the psycho-education group significantly improves caregiver-rated HRQoL of PwND, supporting the feasibility and effectiveness of the psycho-education group.